The Management of Ischemic Priapism Due to Sickle Cell Disease and Other Etiologies: Treatment Strategies and Indications for Penile Prosthesis Implantation in an Endemic Region - Eser Ördek; Sadık Görür; Fatih Gökalp; Duran Kuru; Ferhat Uçurmak (Medicina)
Background and Objectives: Priapism is a condition characterized by a prolonged erection lasting over four hours, either independent of or following sexual stimulation. The primary treatment goal for ischemic and non-ischemic priapism is timely and appropriate intervention in order to preserve erectile function and penile length. This study aims to evaluate the management of recurrent ischemic priapism in sickle cell disease (SCD) patients in an endemic region and compare it with ischemic priapism of other etiologies. Materials and Methods: Patients admitted to our hospital with a diagnosis of priapism between January 2010 and June 2024 were retrospectively reviewed. The patients were divided into two groups: ischemic priapism due to SCD and ischemic priapism due to other etiologies. Patient characteristics, treatment management, and the need for penile prosthesis (PP) were compared. Results: A total of 40 ischemic priapism patients were included in the study; 20 of them had SCD and the other 20 had priapism cases due to different etiologies. In the SCD priapism group, the rate of comorbidity and previous history of priapism were significantly (p < 0.05) higher than in the other etiologies of priapism group. Similarly, in the SCD priapism group, the hospital admission time and the rate of fibrosis findings in MRI (magnetic resonance imaging) were significantly (p < 0.05) higher than in the other priapism groups. The PP implantation rate in the SCD priapism group was found to be significantly (p < 0.05) higher than in the other priapism group. Conclusions: This study highlights the importance of early intervention and patient awareness in SCD-related ischemic priapism, recommending educational programs to improve symptom recognition and prevent complications.